SMART POWER WHEELCHAIR: PROBLEMS AND CHALLENGES OF PRODUCT APPROACH - Ageyev, Serge; Yarovyi, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
This paper focuses on intelligent assistant for power wheelchair (PW) usage in home conditions. Especially in the context of PW intelligent assistant as a consumer product. The main problematic aspects and challenges of smart PW in real application are noted. The approach to formation of system requirements and their classification is offered. The research results proposed and implemented in the ongoing Mobilis project for smart PW. Further prospects of research and development are noted. Also, it is stated that the implementation of smart PW technology opens possibilities to effective integration with new control methods (including brain-computer interfaces).